1999
DOI: 10.1063/1.479855
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene under tensil load: Strain energy storage and breaking of linear and knotted alkanes probed by first-principles molecular dynamics calculations

Abstract: The mechanical resistance of a polyethylene strand subject to tension and the way its properties are affected by the presence of a knot is studied using first-principles molecular dynamics calculations. The distribution of strain energy for the knotted chains has a well-defined shape that is very different from the one found in the linear case. The presence of a knot significantly weakens the chain in which it is tied. Chain rupture invariably occurs just outside the entrance to the knot, as is the case for a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
2
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 30 publications
3
52
2
1
Order By: Relevance
“…We again point to the work of Klein and co-workers [30][31][32][33] who have investigated the effect of topological constraints, including chain entanglements and self-knots, on the rupture strength of the unsaturated carboncarbon bond in n-alkane molecules ranging from n ) 9 to n ) 35. Their work suggests that chains of length greater than n ) 8 should contain topological interchain entanglements, even though they might not exhibit rheological entanglement dynamics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We again point to the work of Klein and co-workers [30][31][32][33] who have investigated the effect of topological constraints, including chain entanglements and self-knots, on the rupture strength of the unsaturated carboncarbon bond in n-alkane molecules ranging from n ) 9 to n ) 35. Their work suggests that chains of length greater than n ) 8 should contain topological interchain entanglements, even though they might not exhibit rheological entanglement dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…[27][28][29] Ab initio molecular dynamics studies have focused on the rupture strength of the carbon-carbon bond in simple n-alkane chains in various conformations but are limited to systems of only a few molecules. [30][31][32][33] Kinetic Monte Carlo methods, 34,35 which are capable of incorporating a variety of failure mechanisms, such as bond rupture and chain slippage, have proven quite useful in modeling the actual experimental tensile strength protocol, but at the outset assume rate laws for the microscopic mechanisms included in the simulation. In such an approach, because the microscopic structure is unknown, a very coarse-grained representation of the amorphous network is employed.…”
Section: Introductionmentioning
confidence: 99%
“…[15] The related results were recently presented for a molecule involving a knot formed by adding an appropriate set of gauche defects to a PM chain. [16] It was found that the large amount of stored energy is located on the bonds at the entrance and exits points of the knot. The presence of the knot weakens the chain in which it is tied and the molecule breaks at a point just outside of the knot.…”
Section: Defectmentioning
confidence: 99%
“…[2,3,5,8,9] Them ost common knot that occurs in polymers is the overhand knot, which is well-known from macroscopic ropes commonly used in sailing and rigging.A lthough the overhand knot is the simplest and smallest knot and consumes the least material, it is known to reduce the strength of the rope by approximately 50 percent. [12][13][14] In polymers,the rupture results in the formation of two radicals,which is attributed to mechanical stress mostly localized in the carbon-carbon bonds at the entry or exit of the knot. Both effects-the weakening of the rope and the rupture in the vicinity of the knot-can also be observed at the molecular level.…”
mentioning
confidence: 99%